Integrative taxonomy of Imparfinis (Siluriformes, Heptapteridae) from the Upper Paraná River basin, Brazil, with description of a new species - Silva, Gabriel S.C. [UNESP]; Reia, Lais [UNESP]; Morimoto, César K. [UNESP]; Benine, Ricardo C. [UNESP]; Oliveira, Claudio [UNESP] (Magnolia Press, 2023)
The Neotropical family Heptapteridae comprises 228 valid species widely distributed in South America. Imparfinis is one of the most diverse genera of this family, with 25 valid species widely distributed, inhabiting streams from Costa Rica to Argentina. Old descriptions coupled with lack of recent systematic studies of the species of Imparfinis from the Upper Paraná river basin have led to a taxonomic impediment and hindered the advancement of studies in other areas, such as ecology, cytogenetic, phylogenetic, and evolution. We conducted the first integrative study analyzing both molecular and morphological data of Imparfinis from the Upper Paraná River basin. Our analyses strongly support the existence of four independent evolutionary lineages in this river system, three of them are the nominal species I. mirini, I. schubarti, and I. piperatus, and a new species from Goiás state described herein.
Keywords: Biodiversity; Catfishes; Neotropical region; Species delimitation